Ámbito hogareño del conejo mexicano (Sylvilagus cunicularius) en un bosque templado del centro de México - Vázquez, Jorge; Farías, Verónica; Rodríguez-Martínez, Luisa; Bautista, Amando; Palacios-Roque, Guadalupe; Martínez-Gómez, Margarita (THERYA, 2013)
The Mexican cottontail rabbit, Sylvilagus cunicularius, is the endemic rabbit with the widest distribution and the largest size (485-515 mm) of all rabbits in Mexico. This cottontail is abundant throughout its range but some populations are declining due to habitat destruction and poaching. In La Malinche National Park (LMNP), Tlaxcala, fires and excessive logging have reduced the habitat (grassland and pine forest) of the Mexican cottontail rabbit. To determine the Mexican cottontail rabbit home range will reveal their spatial ecology, social behavior and infer useful information in the development of programs for conservation. In this work, we investigated the home range size of the Mexican cottontail rabbit and the differences among sexes. The study was developed from May 2006 throughout February 2008 at LMNP, with a sample size of 12 individuals (seven females and five males). The home range size of S. cunicularius averaged 3.62 Â± 0.62 hectares and was not different between males and females (U = 12.0, P = 0.43). Furthermore, home ranges of individuals of S. cunicularius overlapped between individuals of the same sex and of the opposite sex. This is the first formal report of home range size for the Mexican cottontail, which contributes to understand how S.cunicularius uses a grassland habitat (dominated by Muhlenbergia macroura) in a pine forest (Pinus spp.) on the central plateau of Mexico. Key words: Home range, pine forest, Mexico, overlapping, Sylvilagus cunicularius, Tlaxcala.